If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 41 = 6x + 17 Reorder the terms: 41 = 17 + 6x Solving 41 = 17 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 41 + -6x = 17 + 6x + -6x Combine like terms: 6x + -6x = 0 41 + -6x = 17 + 0 41 + -6x = 17 Add '-41' to each side of the equation. 41 + -41 + -6x = 17 + -41 Combine like terms: 41 + -41 = 0 0 + -6x = 17 + -41 -6x = 17 + -41 Combine like terms: 17 + -41 = -24 -6x = -24 Divide each side by '-6'. x = 4 Simplifying x = 4
| 4+(18x-6)= | | 0.008(3-k)+0.08(k-2)=1 | | 34/5-17/10=-51/10 | | 21/10-17/10=19/5 | | 5g+(-8g)= | | 2x+5=10+5 | | 3y+5=y-4 | | 10h-11=59 | | 3(y-2)-5=6-2(y-4) | | 10/7-y=-5/8 | | 5t-7x+3t= | | 10y+4=84 | | 3/2(x+5)-1/4(x+24)=0 | | 98-35= | | -0+5= | | 5x+72=162 | | v=4/33.15*3 | | (X-9/4)=11 | | x+x*2+x+4(x*2)=84 | | 9=2.54i | | (3x+1/2)+(7x-41/2) | | 10X-9=45X+19 | | 2(X+1)=x-8 | | x^6+27y^15=0 | | 9/10z-1=-19/20z+4 | | 18m-2=7m | | -1+0= | | 9/10z-1=19/20z+4 | | z^2-6z+9=12 | | 9M-30=39 | | 5/8-4/5 | | 8m+2=5m-3 |